2020
DOI: 10.19044/esj.2020.v16n15p200
|View full text |Cite
|
Sign up to set email alerts
|

Effet de la salinité sur la germination graines et la croissance des semis de treize cultivars africains de sésame (Sesamum indicum L.)

Abstract: Sesame (Sesamum indicum L.), an annual self-pollinating plant native to Africa and India, is very sensitive to the stages of germination and sowing but moderately tolerant to water and salt stress. The objective of this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The germination rates at the concentrations 400 mM and 500 mM show a significant difference between them and also with those of the concentrations less than or equal to 300 mM. These results agree with those of Dangue et al [19] who showed a significant reduction in the germination rate as a function of salinity in sesame (Sesamum indicum L.).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The germination rates at the concentrations 400 mM and 500 mM show a significant difference between them and also with those of the concentrations less than or equal to 300 mM. These results agree with those of Dangue et al [19] who showed a significant reduction in the germination rate as a function of salinity in sesame (Sesamum indicum L.).…”
Section: Discussionsupporting
confidence: 91%
“…The dry biomass (BS) of peanut variety 73-33 decreased with increasing salt (NaCl) content over the harvest date (Figure 2). This negative effect of NaCl on dry biomass has been noted in various species such as roselle [20], wheat [21], chili [22], cowpea (Phaseolus vulgaris L.) [23], sesame ( [19]; [24]; [25]). This reduction may be related to the toxic effect of Cl − and Na + ions accumulated in the tissues ( [26]; [27]).…”
Section: Discussionmentioning
confidence: 99%